Designing of a generator for wave energy conversion for outdoor activities - Noor Syazana Abd Ghani; Taib Ibrahim; Nursyarizal Mohd Nor (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Wave energy is one of the renewable resources with high availability area of the wave across the world. However, the wave power density in Malaysia is smaller compared to other countries with progressive development in Wave Energy Converter (WEC), which leads to wave energy utilization to produce pico-scale power generation for the benefit of outdoor activities. Thus, this paper is presenting the modeling of a tubular longitudinal permanent magnet linear generator for wave energy conversion for outdoor activities. This research aims to design a pico-scale linear generator with 100 W output power utilizing wave energy. The design is also intended to be a portable design with a weight that less than 20 kg, which compatible with outdoor activities. The generator is proposed by designing the different shapes of permanent magnets with slotless configuration. The designs are simulated using the Finite Element Analysis (FEA) to obtain the performance of flux distribution, flux linkage, and back EMF performance.